Faktor – faktor yang mempengaruhi produktivitas padi sawah di Kecamatan Pemayung Kabupaten Batang Hari - Reno Armando; Uliya Uliya; Tukidi; Enita (PPPM STKIP PGRI Lamongan, 2026)
This study aims to analyze the factors influencing lowland rice productivity in Pemayung District, Batanghari Regency. The factors analyzed include the use of labor, seeds, urea fertilizer, NPK fertilizer, KCl fertilizer, SP-36 fertilizer, and pesticides. A census method was employed, involving 34 farmers as respondents. Data were analyzed using multiple linear regression, preceded by classical assumption tests covering normality, multicollinearity, and heteroscedasticity. The results indicate that the variables of labor, seeds, urea fertilizer, NPK fertilizer, KCl fertilizer, SP-36 fertilizer, and pesticides simultaneously have a significant effect on lowland rice productivity. Individually, the variables of seeds, urea fertilizer, NPK fertilizer, and pesticides significantly affect productivity, whereas labor, KCl fertilizer, and SP-36 fertilizer do not. Based on these findings, it is recommended that farmers pay closer attention to the appropriate use of seeds and fertilizers to enhance lowland rice productivity.